The poor involvement of local youth in the construction workforce in Malaysia / Norizzati Ibrahim - Ibrahim, Norizzati (2014)
The construction industry in Malaysia is heavily dependent on foreign workers. This has resulted in money outflow from this country of about 2.5 million Ringgit Malaysia every year. Unfortunately, it seems that the local youth would prefer to be unemployed rather than be employed in construction sites. Efforts made by the industry and the government to increase youth participation in the construction workforce have been futile. However, positive changes in the construction industry call for a re-assessment of this situation. This study looked into the evolution of the construction industry and the strategies that have been adopted to increase youth participation in the construction workforce. Archival data from the Labor Force Survey Report was compiled to determine the trend of youth participation in the construction workforce. The findings indicate that local youth participation has never exceeded 25% of the total construction workforce. An extensive survey was also carried out on youth at vocational training centers to determine their current perception of a career in the construction industry especially in construction sites. Surprisingly, the findings of the survey found that 3’D (difficult, dangerous and dirty) image is no longer a main factor in distracting local youth from pursuing career in the construction workforce. The main reasons however was found to be lack of encouragement from parents, the abundant presence of foreign workers at construction sites and unattractive wages. The survey also showed that youth are more attracted to the training centers providing non-construction related training programs which provide better facilities and allowances. Construction industry experts were also interviewed to obtain an insight on what went wrong with the previous and current initiatives to attract youth into the construction industry and how things can be done better. Industry experts claimed there was a serious lacking in promotion of career prospects and developments in the construction industry. This shortcoming has perpetuated the negative perception among local youth of the industry being dirty, dangerous and difficult as well as paying low salary. This study has attempted to produce more effective and sustainable strategies that can transform the construction industry into a preferred sector of employment for local youth.